Síntese e cristaloquímica do 1-(4-carboxifenil)-3-(4-acetilamidofenil)triazeno e complexos de cobre(i), prata(I) e ouro(I) com o ligante 1-(4-nitrofenil)-3-(4-etoxicarboxifenil)triazenido - Amaral, Carlos Henrique Oliveira do (2007)
This work deals with the determination of the single crystal structure analysis of four triazenido complexes including gold(I), copper(I), silver(I), and the crystal structure of a free triazene molecule. Crystal data and refinement indices of 1-(4-carboxyphenyl)-3-(4- acetylamidophenyl)triazene (1) are: monoclinic system, space group P21/n, cell parameters a = 7.772(1), b = 9.7365(2), c = 19.55(3) Å, β = 93.435(1)º, Z = 4, R1 = 0.0394, wR2 = 0.0632. The crystal structure show that the molecule deviates significantly from planarity (r.m.s. 0.342 Å). The molecules of (1) are associated to a bi-dimensional supramolecular array in form of helix chains including classic hydrogen bonding in the [010] crystallographic direction. Crystal data and refinement indices of 1-(4-ethoxycarbonylphenyl)-3-(4-nitrophenyl)triazenide(triphenylphosfine)gold(I) (3) are: triclinic system, space group P(-1), cell parameters a = 9.8837(2), b = 12.6159(2), c = 13.0948(2) Å, α = 79,160(1)°, β = 78,411(1)°, γ = 73,731(1)°, Z = 2, R1 = 0.0271, wR2 = 0.0588. One deprotonated triazenido ligand and one triphenylphosfine molecule built the linear coordination geometry of gold(I). Crystal data and refinement indices of 1-(4-ethoxycarbonylphenyl)-3-(4-nitrophenyl)-bis-(triphenylphosfine)copper(I) (4) are: triclinic system, space group P(-1), cell parameters a = 10.9853(2), b = 14.6006(3), c = 16.0638(3) Å, α = 79.160(1)°, β = 78.411(1)°, γ = 73.731(1)°, Z = 2, R1 = 0.0370, wR2 = 0.0996. One deprotonated triazenido ligand and three neutral triphenylfosfine molecules complete the distorted tetrahedral coordination sphere of copper(I). Crystal data and refinement indices of trans-bis-1-(4-ethoxycarbonylphenyl)-3-(4-nitrophenyl)triazenide-bis-(pyridine)silver(I) (5) are: triclinic system, space group P(-1) with cell parameters a = 9.3123(4), b = 11.1234(5), c = 11.1914(5) Å, α = 71.165(3)°, β = 68.723(3)°, γ= 89.530(3)°, Z = 2, R1 = 0.0383 wR2 = 0.0856. Two deprotonated monodentate triazenido ligands and two pyridine molecules in trans position relative to each other in a eight-membered Ag2N6 fragment, perform the Tcoordination geometry of each silver(I) ion. Crystal data and refinement indices of Catena-[bis(μ2-ciano)-bis(triphenilphosfine)-di-silver(I)] (6) are: monoclinic system, space group P21/n with cell parameters a = 9.3174(4), b = 22.931(1), c = 16.1513(8) Å, β = 99.759(3)°, Z = 4, R1 = 0.0526, wR2 = 0.1337. Two neutral triphenilfosfine molecules and two cyanide ligands support the distorted tetrahedral coordination geometry of the silver(I) ion in a open catenated coordination polymer.